2014
DOI: 10.1007/s12032-014-0984-6
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-148b expression is decreased in hepatocellular carcinoma and associated with prognosis

Abstract: MicroRNAs are small non-coding RNA molecules that have been shown to regulate the expression of genes linked to cancer. MicroRNA-148a (miR-148a) has recently been found to be involved in many critical processes in human malignancies. The present study is to clarify the expression pattern and prognostic role of miR-148b in human hepatocellular carcinoma (HCC). The expression of miR-148b was detected in 156 cases of HCC and 36 cases of normal control specimens by real-time PCR. Results showed that miR-148b expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
39
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 37 publications
3
39
0
Order By: Relevance
“…Hepatocellular carcinoma (HCC) is the most common primary liver cancer that is the third cause of cancer-related mortality all over the world [10]. Zhang et al [11] have demonstrated that miR148b had potential ability to suppressor tumor in HCC patients. They suggested that miR-148b has a prognostic value in clinical evaluations [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hepatocellular carcinoma (HCC) is the most common primary liver cancer that is the third cause of cancer-related mortality all over the world [10]. Zhang et al [11] have demonstrated that miR148b had potential ability to suppressor tumor in HCC patients. They suggested that miR-148b has a prognostic value in clinical evaluations [11].…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al [11] have demonstrated that miR148b had potential ability to suppressor tumor in HCC patients. They suggested that miR-148b has a prognostic value in clinical evaluations [11].…”
Section: Introductionmentioning
confidence: 99%
“…In line with these findings, upregulation of miR-214 in various tumor cells increases metastasis formation (2,3,(21)(22)(23). On the other hand, miR-148b is poorly expressed in melanomas and in breast, pancreatic, and hepatocellular carcinomas (1,6,24,25) and its modulation in tumor cell lines reveals its antimetastatic function (6,(26)(27)(28). Here, by modulating miR-214 and miR-148b, respectively, in a negative and positive manner, we show that miR-214 and miR148b are part of a miR-ON-miR regulatory axis where miR-214 favors tumor dissemination following the downregulation of miR-148b and the consequent upregulation of miR-148b direct targets, ITGA5 and ALCAM as well as some of their downstream players (8).…”
Section: Discussionmentioning
confidence: 81%
“…They could bind at the 3′ untranslated region (UTR) of a large number of target genes with imperfect complementarity, resulting in degradation of target messenger RNAs (mRNAs) and inhibition of translation [5]. miRNA dysfunction has been identified in a variety of human diseases including cancer, and a large body of evidence strongly supports the finding that miRNAs play crucial roles in cellular processes such as development, proliferation, differentiation, and apoptosis [6]. Therefore, alteration in miRNA expression is considered to have a part in cancer initiation and progression through regulating the expression of various oncogenes and tumor suppressive genes [7].…”
Section: Introductionmentioning
confidence: 99%